Analisis Pusat Pertumbuhan Ekonomi dan Interaksi Spasial di Provinsi Jawa Tengah - Hari Winarto; bagus Adhitya; agus prabawa (Majalah Imiah Manajemen & Bisnis, 2021)
The purpose of this study is to identify areas that are growth centers and analyze the spatial interactions of the economy between districts/cities in Central Java Province in 2019. The object of this research is 35 districts/cities in Central Java Province. The technique in this research uses scalogram analysis and gravity model analysis. The results of this study are based on the analysis of the scalogram and centrality index in 2019 using 30 types of facilities, resulting in 6 regional hierarchies based on the availability of types of facilities in each district/city. Hierarchy I is the district/city with the most availability of facilities/has the highest centrality value, namely there are 11 districts/cities. In hierarchy II there are 5 districts/cities. Hierarchy III has 7 districts/cities. Hierarchy IV has 6 districts/cities. Hierarchy V and hierarchy VI have 4 and 2 districts/cities, respectively. While the results from the gravity analysis show that Semarang City as one of the growth centers in 2019 has a strong interaction with Semarang Regency, Demak Regency, Kendal Regency, and Grobogan Regency. Keywords: Center for Economic Growth, Scalogram Analysis, Gravity Method Analysis